Spectrophotometric Determination of Gallium(III) and Indium(III) with Some Hydroxy Naphthoic Acid Azo Dyes - Rizk, M.S.; Mohamed, H.A.; Issa, Y.M.; Abu-Agwa, M.M. (Asian Journal of Chemistry, 2010)
A rapid and sensitive spectrophotometric method for the determination of Ga(III) and In(III) has been reported using some hydroxy naphthoic acid azo dyes as reagents. The metal ions react with the mentioned reagents to form 1 : 1, 1 : 2 and 1 : 3 (M : L) complexes. The molecular ratios and the stability constants of the formed complexes are given. The interferences of several ions are reported.